The Complete Genomes of Microcystis ichthyoblabe Kützing and Microcystis protocystis (Crow) Komárek & Anagnostidis Reveal the Complexity and Plasticity of Microcystis Genomes - Jina Kim; Hyaekang Kim; Jaeduk Goh; Seung Won Nam; Eu Jin Chung; Miyoung Shin; Donghyeok Seol; Ki Hwan Kim; Woori Kwak (Microorganisms)
Microcystis is a genus of cyanobacteria responsible for harmful algal blooms (HABs) in freshwater ecosystems, posing significant ecological and public health risks. Despite its importance, current genomic resources are heavily biased toward Microcystis aeruginosa, limiting comprehensive understanding of genomic diversity within the genus. In this study, we present the first complete genome sequences of two morphospecies, M. ichthyoblabe FBCC-A1114 and M. protocystis FBCC-A270. Using long-read sequencing, both genomes were assembled into single circular chromosomes of 5.84 Mb and 5.76 Mb, respectively. Phylogenetic analyses placed both strains within genospecies G, alongside M. aeruginosa and M. viridis. Comparative analysis of biosynthetic gene clusters revealed that, while most genospecies G members harbor aeruginosin, cyanobactin, and microviridin gene clusters, the two newly sequenced strains lack cyanobactin and microcystin clusters but retain the microginin cluster. Synteny analysis demonstrated high structural conservation between the two genomes, while notable structural variations were observed when compared with M. aeruginosa NIES-298. These findings reveal both functional and structural plasticity within the genospecies, suggesting ecotype diversification driven by environmental adaptation. The newly assembled genomes provide critical resources to refine classification frameworks and advance our understanding of Microcystis genomic diversity.